Analisis Perspektif Khalayak Generasi Z Jakarta Terhadap Program Sunset Trip Radio Prambors 102.2 FM - Fanggidae, Michael Sheva Pratama; Abraham, Rendy H (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to analyze the satisfaction and level of interest of Generation Z in Jakarta towards the Sunset Trip program on Radio Prambors 102.2 FM using a qualitative approach with Focus Group Discussion (FGD) as the data collection technique. The research participants are Generation Z individuals residing in Jakarta, and the findings from the FGD will be analyzed to gain a deep understanding of the listeners' perceptions and experiences regarding the Sunset Trip program. This research is expected to provide additional insights into the satisfaction and interest of Generation Z listeners towards radio programs and holds theoretical benefits for the development of communication studies, particularly in the field of radio broadcasting. Additionally, it has practical benefits by offering a reference for other researchers interested in studying radio programs and audience interests. In this context, the S-O-R Theory explains the influence on receivers as a result of communication studies (McQuail, 2000:234), including the impact of voice and intonation in radio broadcasts on listener responses, including attitudes, emotions, and behavioral intentions (Burgoon, Birk, and Pfau, 1990). The Sunset Trip program on Radio Prambors 102.2 FM, with its combination of music, casual conversations, and enjoyable segmentation, provides interactive stimulus to millennial listeners in Jakarta, often referred to as Kaula Muda (KaMu).